Comparative Study and Airspeed Sensitivity Analysis of Full-Wing Solar-Powered UAVs Using Rigid-Body, Multibody, and Rigid-Flexible Combo Models - An Guo; Shanshan Mu; Zhou Zhou; Jiwei Tang (International Journal of Aerospace Engineering)
Solar-powered UAVs are characterized by large-scale, lightweight, and low airspeed, and changes in airspeed lead to wing deformation or stalling, which can easily induce serious flight accidents. A single dynamic model cannot accurately describe this feature, and this airspeed sensitivity can only be analyzed by integrating rigid-body, multirigid-body, and rigid-flexible combo models. This paper proposes a dynamic analysis method for a mixture of rigid-body, multirigid-body, and rigid-flexible combo models, considering the applicable airspeed ranges, computational costs, and structural deformation assumptions of the three models and comparing the differences of modes and responses at different airspeeds, and quantitatively analyzes the effects of airspeed on the motion, deformation, and coupling. The results show that appropriate increase of airspeed is beneficial to the stability of large-scale lightweight platforms, but when it is increased to more than two times the cruise speed, the structural deformation is coupled with the flight dynamic modes, leading to the deterioration of the overall dynamic response. Finally, a mixture of the three models at different airspeeds is proposed, which is necessary for future ultralarge-scale solar-powered UAVs.